2018
DOI: 10.1002/oby.22353
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrant (Ribes nigrum) Prevents Obesity‐Induced Nonalcoholic Steatohepatitis in Mice

Abstract: Objective: With increasing prevalence of nonalcoholic steatohepatitis (NASH), effective strategies to prevent NASH are needed. This study investigated whether the consumption of blackcurrant (Ribes nigrum) can prevent the development of obesity-induced NASH in vivo. Methods: Male C57BL/6J mice were fed a low-fat control diet, a low-fat diet with 6% whole blackcurrant powder, an obesogenic high-fat/high-sucrose control diet (HF), or a high-fat/high-sucrose diet containing 6% whole blackcurrant powder (HF-B) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…In our previous study, we found blackcurrant consumption attenuated obesity-associated inflammation in the liver and LPS-stimulated inflammatory responses of splenocytes in HF diet-fed C57BL/6 mice [12]. As macrophages play a major role in inflammation, we determined whether blackcurrant exerts its anti-inflammatory actions via suppressing inflammatory responses in macrophages using polyphenol-rich BCE.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, we found blackcurrant consumption attenuated obesity-associated inflammation in the liver and LPS-stimulated inflammatory responses of splenocytes in HF diet-fed C57BL/6 mice [12]. As macrophages play a major role in inflammation, we determined whether blackcurrant exerts its anti-inflammatory actions via suppressing inflammatory responses in macrophages using polyphenol-rich BCE.…”
Section: Resultsmentioning
confidence: 99%
“…Increases in total macrophage numbers and the population of pro-inflammatory M1 macrophages in adipose tissue and the liver have been reported as a hallmark of obesity-associated chronic inflammation [9,10,11,12]. As LPS stimulated-inflammatory responses are closely related to M1 polarization [6], we determined whether the anti-inflammatory actions of BCE in macrophages could be attributable to its ability to suppress macrophage polarization to M1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations